An update on the rule and scoring equipment modification issues of the World Taekwondo (WT) competition system - Moenig, U.; Kim, M.; Choi, H.; Sim, S. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background. A couple of earlier studies described the rule and scoring equipment modification issues of the World Taekwondo (WT) competition system, initiated after the turn of the millennium as a result of multiple scandals and irregularities concern- ing match- fixing, lack of transparency, and nepotism in taekwondo institutions. Moreover, taekwondo matches were generally perceived as not being interesting to watch for spectators. However, these earlier studies were highly critical of the Protector & Scoring System (PSS) and the complicated, ever-changing Competition Rules and Interpretations, introduced progressively as a consequence of these issues and scandals. Problem and Aim. This study aims to find out if taekwondo experts support the criticism voiced in these earlier studies. Method. This present study puts the criticism voiced in these articles to the test by means of an anonymous survey of relevant taekwondo experts, such as (present and former) national team coaches and domestic (South) Korean middle-, high school, and university team coaches. Results. The survey provides mixed results; on some issues, the results are in agreement with the criticism expressed in the ear- lier studies, but on other positions, they diverge. The most important findings are that the majority of coaches prefer the PSS to a conventional, human judging system, despite the negative effects of the PSS on taekwondo techniques applied in competitions. In agreement with findings in previous articles, the majority of coaches perceive the general competition rules as too complicated, but they strongly support the present, multiple points scoring rules. Conclusion. The domestic Korean coaches appear relatively satisfied with the state of affairs of domestic and international taek- wondo institutions. On the other hand, half of the national team coaches, especially the non-Asian ones, are not pleased with their domestic taekwondo federations, but, are generally also supportive of the WT leadership and the Kukkiwon.